Federated Learning for Privacy-Preserving AI in Hybrid Clouds: A Technical Overview - Sunil Kumar Gosai, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Federated Learning (FL) represents a transformative approach to machine learning in hybrid cloud environments, addressing critical challenges in data privacy and security while enabling collaborative model training across distributed environments. This comprehensive technical overview explores the architecture, implementation, and benefits of FL in hybrid cloud deployments. The article explores how organizations can leverage FL to maintain data sovereignty while achieving comparable or superior model performance to traditional centralized approaches. By analyzing various aspects including communication optimization, model initialization, local training, and global aggregation, this article demonstrates FL's effectiveness in preserving privacy while enabling cross-organizational collaboration. The article encompasses privacy preservation mechanisms, security protocols, and scalability considerations, providing insights into both current capabilities and future directions for enterprise implementations.
Keywords: Federated Learning; Hybrid Cloud Computing; Machine Learning; Privacy Preservation; Secure Data Processing